2023
DOI: 10.5551/jat.64159
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implication of Consistently Strict Phosphate Control for Coronary and Valvular Calcification in Incident Patients Undergoing Hemodialysis

Abstract: Aims: Serum phosphate control is crucial for the progression of vascular and valvular calcifications. Strict phosphate control is recently suggested; however, there is a lack of convincing evidence. Therefore, we explored the effects of strict phosphate control on vascular and valvular calcifications in incident patients undergoing hemodialysis.Methods: A total of 64 patients undergoing hemodialysis from our previous randomized controlled trial were included in this study. Coronary artery calcification score (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…Furthermore, hyperphosphatemia was shown to be positively associated with CAC in patients with CKD [ 21 ]. Consistently strict phosphate control may slow the progression of coronary and valvular calcifications in incident patients undergoing hemodialysis [ 33 ]. In our study, we found that the Ca × P product was an independent risk factor for severe CAC.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, hyperphosphatemia was shown to be positively associated with CAC in patients with CKD [ 21 ]. Consistently strict phosphate control may slow the progression of coronary and valvular calcifications in incident patients undergoing hemodialysis [ 33 ]. In our study, we found that the Ca × P product was an independent risk factor for severe CAC.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that the management of serum P can play a signi cant role in weight loss in individuals and chronic diseases [11,37]. Assessment of serum P levels is essential in patients with hypothyroidism, because elevated serum phosphorus levels may increase the disease complications and be associated with microvascular dysfunction [38], coronary artery calci cation [39], chronic kidney disease [40], and cardiac arrest [41].…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the benefits of phosphate-lowering medication on VC, arterial stiffness, and clinical outcomes in predialysis CKD stages remain uncertain [ 33 , 34 ]. Nevertheless, there is evidence in favor of phosphate lowering; a recent Japanese study has proven that consistently strict phosphate control may slow the progression of coronary and valvular calcifications in incident patients undergoing HD ( Table 1 ) [ 35 ].…”
Section: Phosphorus Vitamin D and Calcium And Vascular Calcification ...mentioning
confidence: 99%
“…Yet, the benefits of phosphate-lowering medication on VC, arterial stiffness, and clinical outcomes in predialysis CKD stages remain uncertain [33,34]. Nevertheless, there is evidence in favor of phosphate lowering; a recent Japanese study has proven that consistently strict phosphate control may slow the progression of coronary and valvular calcifications in incident patients undergoing HD (Table 1) [35]. RCT on 120 HD patients given supplements of vitamin K2, vitamin K1, and placebo Matrix Gla protein levels Matrix Gla protein levels showed a significant increase in the vitamin K2 group compared with vitamin K1 and placebo groups Li 2017 [44] 100 HD patients Used vitamin-K-enriched dialysate Decreased VC scores as the effect of vitamin K In PROGREDIR study on non-dialysis CKD patients, Machado et al demonstrated that an increased intake of phosphorus-and calcium-rich food is associated with coronary artery calcification (Table 1) [36].…”
Section: Phosphorus Vitamin D and Calcium And Vascular Calcification ...mentioning
confidence: 99%